Creativity and Life Satisfaction in Spanish University Students. Effects of an Emotionally Positive and Creative Program - Caballero-García, Presentación A.; Sánchez Ruiz, Sara (Frontiers in Psychology, 2021)
There is an increasing demand by society that university students demonstrate competitive skills to enable them to achieve greater success when entering the workplace. Creativity and life satisfaction correlate positively with academic performance, productivity, and excellence in the working environment. The presence of creativity and emotional intelligence in the curriculum and teaching methods in Spanish universities, however, is surprisingly lacking. Studies that analyse gender differences in these variables provide conflicting results. The purpose of our research is to analyse the individual differences in creativity and life satisfaction in students, and the changes produced by a positive emotional and creative intervention. The methodology used was a quasi-experimental pre- test / post- test design with experimental/control groups. Three hundred university students (23% men and 77% women) from the Community of Madrid (Spain) completed three exercises that evaluated creativity (Creative Intelligence, by Corbalán et al., 2003) and life satisfaction (Satisfaction with Life Scale, by Diener et al., 1985, and Overall Life Satisfaction Scale, by Campbell et al., 1976). The results show significantly higher results in creativity and life satisfaction in women, who continued to achieve high results after the intervention. Finally, we discuss the need for emotional and creative education in universities and focus on the employability and the guarantee of equal opportunities through the development of these competencies.